Saudi Arabia and Nuclear Weapons How do countries think about the bomb? - Cigar, Norman L. (UCLA Center for Middle East development (CMED) series, 2016)
Nuclear proliferation in the Middle East remains an issue of concern. Saudi Arabia's actions will largely rest on Iran's decisions, and discussions and preparations within Saudi Arabia would suggest that it is ready to react to potential shifts in the region's nuclear powers. A comprehensive study of Saudi Arabia's attitude to nuclear weapons, this book offers an exploration of nuclear proliferation that would interest students, scholars and policymakers working in Middle East studies, as well as Military and nuclear proliferation studies.